2020
DOI: 10.1161/atvbaha.120.314360
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages Promote Aortic Valve Cell Calcification and Alter STAT3 Splicing

Abstract: Objective: Macrophages have been described in calcific aortic valve disease, but it is unclear if they promote or counteract calcification. We aimed to determine how macrophages are involved in calcification using the Notch1 +/− model of calcific aortic valve disease. Approach and Results: Macrophages in wild-type and Notch1 +/− … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…In this study, initial experiments under static conditions revealed that human VEC sense type I and II IFNs, which triggers the activation of STAT1 and NF-κB, and the subsequent expression of inflammatory mediators. Additional pathways, like STAT3, could also play a role in JAK/STAT signaling in valve cells, given that macrophage recruitment promotes calcification and alters STAT3 splicing in the Notch1(+/−) model of CAVD [ 34 ]. The disease occurs in a side-specific manner, likely mediated by the significant differences in hemodynamic forces experienced by each side of the aortic valve [ 1 , 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, initial experiments under static conditions revealed that human VEC sense type I and II IFNs, which triggers the activation of STAT1 and NF-κB, and the subsequent expression of inflammatory mediators. Additional pathways, like STAT3, could also play a role in JAK/STAT signaling in valve cells, given that macrophage recruitment promotes calcification and alters STAT3 splicing in the Notch1(+/−) model of CAVD [ 34 ]. The disease occurs in a side-specific manner, likely mediated by the significant differences in hemodynamic forces experienced by each side of the aortic valve [ 1 , 4 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest a potential interplay between inflammatory cytokines and oscillatory flow on monocyte adhesion that may be relevant to CAVD. In fact, infiltrated monocyte-derived cells, such as macrophages, are enriched in calcified valves and show increased inflammatory and osteogenic activity [ 34 , 49 , 50 ]. Moreover, the enrichment of polarized macrophages in bicuspid valves and the activation of macrophages by cyclic mechanical strain in several models suggest a potential role for mechanical strain in macrophage activation and the ensuing inflammation in CAVD [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show Htr2b ablation nor receptor inhibition alter Runx2 expression or osteogenic calcification, suggesting the hemodynamic phenotype observed in mutant mice is not based on canonical osteogenic signaling pathways (Fig 6). Immune cell recruitment plays a key role in other 5-HT 2B -mediated fibrotic disease and has been shown to contribute to the Notch1 +/model of CAVD, suggesting it may be involved here [25,30,39]. This may also indicate a phenotype arising from cells other than myofibroblasts.…”
Section: Plos Onementioning
confidence: 99%
“…These clinical and basic research findings led us to hypothesize that 5-HT 2B may be a novel target for pharmacological treatment of CAVD. Therefore, we evaluated the impact of both genetic and pharmacological ablation of 5-HT 2B in the well-established Notch1 +/mouse model of CAVD, based on the heritable form in patients with NOTCH1 mutations [21][22][23][24][25]. Briefly, we found that genetic ablation mitigated CAVD phenotypes, while pharmacological targeting was not efficacious.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the phosphates required to generate mineral depositions, inorganic phosphates have been shown to regulate expression of proteins such as BMP2 and osteopontin [31,32]. Studies using in vitro models have demonstrated the important role of mechanical stress, the influence of the matrix and the interaction between VICs, VECs and macrophages in the process of calcification [5,7,[33][34][35][36][37]. These studies thereby demonstrated that the absence of the complete valvular structure might prevent drawing accurate conclusions for in vivo calcification.…”
Section: Introductionmentioning
confidence: 99%